Comparing future patterns of energy system change in 2 °C scenarios with historically observed rates of change. (November 2015) - van Sluisveld, Mariësse A.E.; Harmsen, J.H.M.; Bauer, Nico; McCollum, David L.; Riahi, Keywan; Tavoni, Massimo; Vuuren, Detlef P. van; Wilson, Charlie; Zwaan, Bob van der
Highlights: This paper systematically compares modeled rates of change to historical references. The indicators tested vary in terms of system focus, timeframe and normalization. Indicators that look into absolute change reach unprecedented levels by 2030. Indicators that account for overall system growth remain within historical records. The indicators provide no conclusive insights into the achievability of 2 °C scenarios. Abstract: This paper systematically compares modeled rates of change provided by global integrated assessment models aiming for the 2 °C objective to historically observed rates of change. Such a comparison can provide insights into the difficulty of achieving such stringent climate stabilization scenarios. The analysis focuses specifically on the rates of change for technology expansion and diffusion, emissions and energy supply investments. The associated indicators vary in terms of system focus (technology-specific or energy system wide), temporal scale (timescale or lifetime), spatial scale (regional or global) and normalization (accounting for entire system growth or not). Although none of the indicators provide conclusive insights as to the achievability of scenarios, this study finds that indicators that look into absolute change remain within the range of historical growth frontiers for the next decade, but increase to unprecedented levels before mid-century. Indicators that take into account or normalize for overall system growth find future change to be broadly within historical ranges. This is particularly the case for monetary-based normalization metrics like GDP compared to energy-based normalization metrics like primary energy. By applying a diverse set of indicators alternative, complementary insights into how scenarios compare with historical observations are acquired but they do not provide further insights on the possibility of achieving rates of change that are beyond current day practice.